The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11239-012-0849-9
|View full text |Cite
|
Sign up to set email alerts
|

TNFSF4 gene polymorphism rs3861950 but not rs3850641 is associated with the risk of cerebral infarction in a Chinese population

Abstract: Tumor necrosis factor superfamily member 4 (TNFSF4) plays a key role in the process of atherosclerosis, a common risk factor for both myocardial and cerebral infarctions. Recent studies indicate that the single nucleotide polymorphism (SNP) rs3850641 in TNFSF4 is associated with higher risk of myocardial infarction, but little is known about the association between TNFSF4 variation and cerebral infarction (CI). A case-control study involving 385 CI patients and 385 age-matched, sex-matched non-CI controls was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Wang et al have assessed the associations between rs3861950 T > C and rs1234313 A > G polymorphisms with CAD risk (Wang et al, 2019). Six studies were evaluated in Wang's meta-analysis for rs3861950 T > C (Wang et al, 2005;Koch et al, 2008;Cheng et al, 2011Cheng et al, , 2015Feng et al, 2013) and another six for rs1234313 A > G (Wang et al, 2005;Koch et al, 2008;Cheng et al, 2011Cheng et al, , 2015Huang et al, 2014Huang et al, , 2016. However, sufficient data was only available in 4 studies, both for rs3861950 T > C (Koch et al, 2008;Cheng et al, 2011;Feng et al, 2013) and rs1234313 A > G ( Koch et al, 2008;Cheng et al, 2011;Huang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al have assessed the associations between rs3861950 T > C and rs1234313 A > G polymorphisms with CAD risk (Wang et al, 2019). Six studies were evaluated in Wang's meta-analysis for rs3861950 T > C (Wang et al, 2005;Koch et al, 2008;Cheng et al, 2011Cheng et al, , 2015Feng et al, 2013) and another six for rs1234313 A > G (Wang et al, 2005;Koch et al, 2008;Cheng et al, 2011Cheng et al, , 2015Huang et al, 2014Huang et al, , 2016. However, sufficient data was only available in 4 studies, both for rs3861950 T > C (Koch et al, 2008;Cheng et al, 2011;Feng et al, 2013) and rs1234313 A > G ( Koch et al, 2008;Cheng et al, 2011;Huang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 161 papers were initially obtained from PubMed, Web of Science, EBSCO, CNKI, and Google Scholar using the keywords search before February 2020. Among these studies, 150 articles were further excluded using the selection criteria described above and 11 of the articles (Wang et al, 2005;Koch et al, 2008;Cheng et al, 2011Cheng et al, , 2015Ria et al, 2011;Feng et al, 2013;Huang et al, 2014Huang et al, , 2016Jiang et al, 2019;Huang) were included for quality assessment and evaluation of the Hardy-Weinberg equilibrium (HWE) (Thakkinstian et al, 2005). Finally, the 11 eligible articles containing nine studies of rs3861950 T > C and nine studies of rs1234313 A > G were included based on NOS scores >5 (Supplementary Table 3).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…IL1B took part in 5 pathways, and IL6 took part in 4 pathways which are NOD-like receptor signalling pathways, cytokine-cytokine receptor interactions, TNF-signalling pathway, and Rheumatoid arthritis pathways; CXCL1, CXCL2, and CXCL3 took part in 2-3 pathways including the TNF-signalling pathway, cytokine-cytokine Sex specific signaling analysis of ischemic stroke receptor interactions, and NOD-like receptor signalling pathways. Several studies have shown that immune responses including IL6 [34], IgA [35], CXCL16 [36], TNFSF4 [37], and IL10 [38] were involved in stroke. IL6 and infarction size were reported as independent predictors of short-term stroke outcome in young Egyptian adults [34].…”
Section: Discussionmentioning
confidence: 99%
“…The study recruited ethnically Han Chinese patients with ACI, diagnosed according to the classification of acute stroke. 15,2426 Patients were recruited from the Department of Neurology, Xiangya Hospital, Central South University, Changsha, China, between June 2007 and December 2012. ACI was diagnosed via brain magnetic resonance imaging, magnetic resonance angiography, carotid artery ultrasonography, ophthalmoscopy and cardiac colour ultrasonography, and was confirmed by at least two neurologists.…”
Section: Methodsmentioning
confidence: 99%
“…15,[24][25][26] The presence of carotid atherosclerotic plaque was defined as an area of focal wall thickening more than 50% greater than surrounding wall thickness. 18,22 The control population included age-and sex-matched unrelated subjects undergoing routine health screening at Xiangya Hospital during the same period.…”
Section: Study Populationmentioning
confidence: 99%